Purification and characterization of protease from mangroves derived strain of Bacillus cereus - K. Saravanakumar2, P. Senthilraja1* and (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Protease enzymes of most potent strain, bacillus cereus, were purified in 2-step procedures involving ammonium sulfate precipitation, sephadex G-200 and sephadex G-100 gel permeation chromatography. The purification steps of proteases specific activities of 727.4 u/mg protein/ml. The maximum protease activities for enzymes were attained at 30 0C, pH 7.2, 1% of chitin concentration and 0.4 enzyme concentrations. The obtained data showed that the purified proteases were different enzymes not identical ones. It was suggested that applications of protease of the present purified enzymes in the fields of pharmacy, chemotherapeutic agents and/or industrial purposes and this suggestion, however, needs further investigation. <div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; margin-left: 32.3pt; border-left: medium none; margin-right: 34pt; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"><p class="abstract" style="margin: 6pt 0in 0pt; text-align: left; mso-padding-alt: 0in 0in 1.0pt 0in; mso-para-margin-top: 6.0pt; mso-para-margin-right: 0in; mso-para-margin-bottom: .0001pt; mso-para-margin-left: 3.23gd; mso-border-bottom-alt: solid windowtext .5pt; padding: 0in;" align="left">Ã‚Â 